Time in the Twelfth Century (Interfaces: A Journal of Medieval European Literatures, 2023)
Guest editors Sarah Bowden, Lea Braun and George Younge introduce Issue No. 10 of Interfaces: A Journal of Medieval European Literatures, dedicated to the theme of 'Time in the Twelfth Century,' and offer a general overview of the matter and contents of the contributions.
Keywords: Time; Eternity; Medieval Literature; Narration; Representation; Twelfth Century; Europe; Middle Ages; Comparative Litarature